Quantifying impacts of biomass feedstock attributes in optimizing tropical biorefineries: case of Peninsular Malaysia - Ong, Chulee; Roda, Jean Marc (Elsevier, 2025)
Amid growing global energy demands and climate concerns, sustainable biofuels offer a key alternative to fossil fuels. This study quantifies the impacts of spatial fragmentation, moisture content, resource yield density, and sourcing strategies on biofuel production costs and scalability in Peninsular Malaysia. Oil palm fronds with high moisture and fragmentation and reduced capacity by 36 % compared to rice straw. Single-feedstock systems like palm press fiber proved more cost-effective unless moisture in multi-feedstock combinations was reduced. For example, a PPF-EFB combination with 48.1 % moisture is 31 % cheaper than EFB alone at 60 % moisture. These results emphasize early-stage moisture management through mobile drying units or pre-treatment hubs are essential for economic viability. By benchmarking against crude oil prices, this study challenges assumptions about multi-feedstock cost savings and offers actionable insights for building scalable, cost-effective tropical biofuel supply chains.